UNITY AND DIFFERENTIATION OF LABOUR DISPUTES AND CONFLICTS OF INTEREST: PRIVATE AND PUBLIC BEGINNINGS (EUROPEAN AND ASIAN LAW REVIEW, 2023)
The article examines the issues of correlation of labour disputes and conflicts of interest in labour legislation and regulations on the civil service. The main positions on the inclusion or non-inclusion of service relations in the area of labour law are presented, based on this, the conclusion is reproduced that contracts on labour (service) with public employees are special classes of labour contracts, and the passage of public service is, as it were, in a state of bifurcation, branching, division into parts (bifurcation). This article contains a discussion about whether it is possible to justify the emergence of labour disputes (conflicts) in official relations affecting private and public interests, in this regard, common features, principles inherent in labour disputes and conflicts of interest are analyzed, their differences in subject composition are revealed. Finally, the author concludes that it is possible to combine labour disputes and conflicts of interest in a single definition of the concept – labour disputes (conflicts), with their subdivision into labour disputes (conflicts) of certain categories of workers and labour disputes of public employees.
Keywords: labour dispute; conflict of interests; unity and struggle; labour dispute (conflict) in service relations; private and public interest